Abnormal lysine acetylation with postovulatory oocyte aging. (4th December 2013) - Lee, Ah Reum; Thanh Ha, Le; Kishigami, Satoshi; Hosoi, Yoshihiko
Abstract: Background: A postovulatory mammalian oocyte decreases developmental potential with in vivo aging in the oviduct or in vitro aging in the culture dish. The mechanism underlying oocyte aging still largely remains an enigma. Accumulating data suggest that the epigenetic alterations such as histone acetylation are also associated with postovulatory aging. Objective: To perform a review evaluating a new aspect of oocyte aging in terms of the epigenetic alterations focusing on lysine acetylation. Methods: In addition to a search of the literature in Pubmed, we introduced our recent published data. Results: Histone acetylation in the mouse oocyte increases during aging, potentially impacting gene regulation in the subsequent embryonic development. Oocyte aging results in increased acetylation of alpha‐tubulin, a non‐histone protein, and nicotinamide, an inhibitor of class III HDAC, partially prevents some of oocyte aging phenotypes. Conclusion: Abnormal regulation of protein acetylation itself is suggested in oocyte aging and could contribute to the aging phenotypes.